Editorial Foreword - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Yahaya, Mohammad Hafiz; Taharuddin, Nurul Shima; Md Nazri, Haslinda; Rosman, Muhammad Redza BIN; Nazrin, Nizar (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020), 2020)
We are very pleased that IDEALOGY JOURNAL is presenting its 5th volume and 2nd issue. We are also very excited that the journal has been attracting papers from a variety of advanced and emerging countries such as Indonesia, Pakistan, Saudi Arabia, Bangladesh, etc. The variety of submissions from such countries will help the aimed global initiatives of the journal.